Science diplomacy as a form of cooperation and rivalry in the Arctic - Łuszczuk, Michał (Teka Komisji Politologii i Stosunków Międzynarodowych, 2018)
In the context of the challenges posed by the intensifying effects of climate change and the growing international importance of the Arctic, the question about relationship between scientists and diplomats and political decision-makers in process of shaping and implementing foreign policy has been emerging. This article – based on the concept of scientific diplomacy and analysis of selected examples of interactions between the world of science and world of foreign policy in the Arctic region – indicates the two-dimensional nature of a scientific diplomacy. On the one hand, there is a national dimension – oriented towards the realization of state’s own interests and on the other there is an international dimension oriented towards developing regional cooperation and solving common problems. This specific nature of scientific diplomacy means that it can be perceived both as a instrument of rivalry and a mechanism of cooperation in contemporary international relations. W kontekście wyzwań wynikających z nasilających się następstw zmian klimatu oraz wzrostu międzynarodowego znaczenia regionu Arktyki pojawia się istotne zagadnienie specyfiki relacji zachodzących współcześnie między naukowcami a dyplomatami oraz politykami w zakresie kształtowania oraz realizowania polityki zagranicznej państwa. W artykule w oparciu o koncepcję dyplomacji naukowej oraz analizę wybranych przykładów interakcji pomiędzy światem nauki oraz polityki zagranicznej w Arktyce wskazuje się na dwuwymiarowy charakter dyplomacji naukowej. Z jednej strony jest to wymiar narodowy – ukierunkowany na realizację partykularnych interesów państw, z drugiej zaś wymiar międzynarodowy – służący rozwojowi współpracy regionalnej i rozwiązywaniu wspólnych problemów. Ta specyficzna natura dyplomacji naukowej oznacza, iż stanowić może ona we współczesnych stosunkach międzynarodowych zarówno instrument rywalizacji, jak też mechanizm współpracy.